The Barnabáš Kos Case Based on a Novel by Peter Karvas - Solan, Peter; Biath, Tibor; Kemr, Josef; Košťová, Jarmila; Sarvašová, Hana (Slovenský filmový ústav, 2018)
In this bitingly satirical film Peter Slovan, a continuous source of trouble for the film functionaries of the socialist Slovakia, tackles an evergreen topic - the corruptive effects of power. Barnabáš Kos, a triangle player at a symphonic orchestra, is suddenly promoted to serve as the head of the said institution, even though both he and his superiors deem him completely unfit for the task. Encouraged in equal parts by this unexpected recognition and the servile praise of his colleagues, Kos's modesty starts to gradually vanish. The erstwhile bashful and aloof percussionist quickly becomes aware of the advantages of his new office, and begins to realise his increasingly ludicrous artistic ambitions. Ultimately, the submissive marionette turns into a source of public humiliation, and his astonishing career finds an abrupt end. Orchestra serves here as a microcosm that grotesquely reflects the absurd and tragicomic mechanisms of the paranoid apparatus of power. [letterboxd.com]